Weg met die wit "Dubula iK****r" - Die Stem: onversoenbare standpunte rakende Suid-Afrika se nasionale volkslied soos weergegee in persberigte - Moll, Johan (Faculty of Humanities, University of the Free State, 2017)
Although it was initially accepted that the inclusion of Die Stem in the national anthem was part of the compromise reached during the founding of the new democratic state of South Africa in 1994, many black people, and especially young blacks, are unapologetic and insistent in their demands for complete transformation. Consequently, cries for the removal of Die Stem (closely associated with apartheid) from the national anthem, Nkosi Sikele’ iAfrica (in short Nkosi), have grown stronger, as is pointed out in this article, “Down with the white “Dubula iK****r” – Die Stem: Irreconcilable views regarding South Africa’s national anthem as presented in press reports”. Objections against the national anthem are widespread, and it emanates from many segments of the population. Agnostics and atheists object to the fact that their views are not taken into consideration or respected. Some musicologists complain that the melody of Nkosi’ is prayer-like, in contrast to the triumphal march music of Die Stem. This article concludes by proferring possible resolutions in adopting a national anthem that could promote greater inclusivity, seeing that most whites show scant enthusiasm for the Nkosi’ lyrics. They, unfortunately, distance themselves from African languages, while many black people reject the preference given to only three of the country’s indigenous languages. One solution would be to change the national anthem to a purely instrumental presentation. This would entail the appointment of a representative overview panel, with an appropriate prize for best composition; the latter with the difficult commission of including elements from all South African languages’ most important songs. Another solution would be to follow Zambia’s example with only English lyrics in the national anthem. The question, however, is whether there is sufficient tolerance in this country to view with empathy all the legitimate protests raised against the South African national anthem. For the sake of greater unity, sacrifices will have to be made by all to respect exclusivity, giving every voice a chance to be heard, to eventually mesh this into a new whole, and in earnest follow the liberating road to an inclusive national anthem.
Keywords: Die Stem; Nkosi Sikele' iAfrica (Nkosi); Objections; Defence; Economic Freedom Fighters (EFF); Steve Hofmeyr; Culture; Unity; English